Establishing an In Vitro 3D Spheroid Model to Study Medulloblastoma Drug Response and Tumor Dissemination. Issue 1 (26th January 2022) - Roper, Sophie J.; Coyle, Beth
Abstract: Medulloblastoma is the most common malignant pediatric brain tumor. Current treatment involves surgery, chemotherapy, and craniospinal radiotherapy, and these are associated with a significant reduction in quality of life. Metastatic dissemination at diagnosis is found in up to 30% of medulloblastoma cases and, alongside therapy resistance, is a significant feature in determining poor outcome. Development of new therapeutic approaches requires models where drug resistance and migration can be readily quantified and that are representative of patient disease. 3D medulloblastoma (3D‐MB) spheroids are a simple yet effective means of bridging the gap between 2D culture and in vivo methods, providing users with highly reproducible in vitro models that more accurately recapitulate tumor morphology, drug response, and migration from a tumor mass. Unlike other cancer types, medulloblastoma spheroids fail to grow in their different standard cell culture media; instead, each cell line requires the same stem cell–enriching conditions. This requirement, however, has the advantage that it allows direct comparison of growth and response between cell lines in the absence of any potential media bias. In addition, spheroids can be used to model the initial stages of metastatic dissemination, something that cannot be achieved in 2D culture, providing insight into key changes occurring in migratory cells. Here, we provide protocols that detail the initial generation and maintenance of 3D‐MB spheroids from sonic‐hedgehog, Group 3, and Group 4 medulloblastoma subgroups, as well as describing functional assays to study drug response and cell migration across hyaluronan matrices, which represent the extracellular matrix backbone of the brain parenchyma. Through application of these simple yet highly representative models, it will be possible to test novel therapeutics targeting metastasis and drug resistance, as well as to develop insights into the mechanistic processes driving relapse in this malignant pediatric brain tumor. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation and maintenance of 3D medulloblastoma (3D‐MB) spheroids Support Protocol 1 : Measuring spheroid size for coefficient‐of‐variation analysis Basic Protocol 2 : Assessing drug response in 3D‐MB spheroids Support Protocol 2 : 384‐well 3D‐MB spheroid generation Basic Protocol 3 : Immunohistochemical staining of 3D‐MB spheroids Basic Protocol 4 : Modeling metastatic dissemination using 3D‐MB migration models Support Protocol 3 : RNA extraction from 3D‐MB spheroids